Capacitive Deionization: Rapid Inversion of Surface Charges in Heteroatom‐Doped Porous Carbon: A Route to Robust Electrochemical Desalination (Adv. Funct. Mater. 9/2020). (26th February 2020) - Kang, Jin Soo; Kim, Seoni; Chung, Dong Young; Son, Yoon Jun; Jo, Kyusik; Su, Xiao; Lee, Myeong Jae; Joo, Hwajoo; Hatton, T. Alan; Yoon, Jeyong; Sung, Yung‐Eun
Abstract : In article number 1909387, Jeyong Yoon, Yung‐Eun Sung, and co‐workers report capacitive deionization using heteroatom‐doped porous carbons prepared from coffee waste. The presence of nitrogen and sulfur dopants lead to rapid inversion of surface charges in the carbonaceous electrodes during desalination, which leads to high performance and stability. Roles of the dopants are revealed by diverse electrochemical and synchrotron‐based X‐ray analyses.